Identifikasi Telur Cacing Nematoda Usus Pada Feses Anak Usia 5-10 Tahun - Fitriani Kahar; Quirinus Efendi; Ichsan Hadipranoto (Jaringan Laboratorium Medis, 2020)
Humans are the host of several intestinal nematodes, most of which can cause public health problems. Among intestinal nematodes there are species that are transmitted through soil or called "soil transmitted helmith" can occur in species Ascaris lumbricoides, Ancylostoma duodenale, Trichuris trichiura. These nematodes mostly infect children aged 5-10 years. The purpose of this study was to determine the presence of intestinal nematodes in the stools of children aged 5-10 years who live around Jalan Abdul Kadir Makassar City, and this study was conducted in the D-3 laboratory of Health Analysts at the University of Eastern Indonesia Makassar with the sedimentation method. The research conducted was a laboratory observation. From examination data on 20 faecal samples of children aged 5-10 years, 7 positive samples (35%) were found, namely Ascaris lumbricoides and 1 positive sample (5%) Trichuris trichiura. From the results of the above research it is suggested to children to maintain hygienic and environmental sanitation. It is recommended to further researchers to examine Ascaris lumbricoides worms and trichuris tricura quantitative methods to measure the amount of intestinal worms infection.